2009
DOI: 10.1172/jci36175
|View full text |Cite
|
Sign up to set email alerts
|

TREM-like transcript-1 protects against inflammation-associated hemorrhage by facilitating platelet aggregation in mice and humans

Abstract: Triggering receptor expressed on myeloid cells-like (TREM-like) transcript-1 (TLT-1), a type 1 single Ig domain orphan receptor specific to platelet and megakaryocyte α-granules, relocates to the platelet surface upon platelet stimulation. We found here that patients diagnosed with sepsis, in contrast to healthy individuals, had substantial levels of soluble TLT-1 (sTLT-1) in their plasma that correlated with the presence of disseminated intravascular coagulation. sTLT-1 bound to fibrinogen and augmented plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(158 citation statements)
references
References 38 publications
(34 reference statements)
6
152
0
Order By: Relevance
“…Platelets from these mice are defective in aggregation in response to adenosine diphosphate and U46619 stimulation. 36 TLT-1 is part of a family of receptors termed triggering receptors expressed on myeloid cells (TREMs) 37 ; and although TLT-1 is homologous to TREMs in its V-type immunoglobulin-like extracellular domain, TLT-1 has a longer cytoplasmic tail with a proline-rich region and contains an ITIM instead of an immunoreceptor tyrosine-based activation motif (Figure 3). It has been shown in vitro that the ITIM region of TLT-1 is capable of being phosphorylated and can recruit SH2-domain-containing protein tyrosine phosphatases 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets from these mice are defective in aggregation in response to adenosine diphosphate and U46619 stimulation. 36 TLT-1 is part of a family of receptors termed triggering receptors expressed on myeloid cells (TREMs) 37 ; and although TLT-1 is homologous to TREMs in its V-type immunoglobulin-like extracellular domain, TLT-1 has a longer cytoplasmic tail with a proline-rich region and contains an ITIM instead of an immunoreceptor tyrosine-based activation motif (Figure 3). It has been shown in vitro that the ITIM region of TLT-1 is capable of being phosphorylated and can recruit SH2-domain-containing protein tyrosine phosphatases 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, septic platelet activation can facilitate the production of both pro-and antiinflammatory cytokine networks (26). The nature of this platelet activation is characterized by increased surface Pselectin expression (27,28); increased levels of a granulereleased factors in plasma, such as soluble P-selectin (29); and increased levels of triggering receptor expressed on myeloid cells-like transcript-1 (30) or PF-4 in mice (31). Clark et al (6) also showed a novel mechanism of platelet-neutrophil interaction that leads to enhanced bacterial trapping during sepsis.…”
Section: Platelets and Pathogensmentioning
confidence: 99%
“…Tails were cut 2.0 mm from the end and were immersed in prewarmed PBS. Tail bleeding time was determined as previously described 24 and was recorded as the time required from the start of bleeding to the cease of bleeding. The body weight of each mouse was measured at baseline and at the end of the 6-week study.…”
Section: Tail Bleeding Time Assaymentioning
confidence: 99%